Laporan Pertama tentang Penyakit Busuk Arang pada Kacang Tanah - Suryo Wiyono; Widodo . (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Peanut charcoal rot disease was first observed in Bogor,West Java in June 2010, and Serang, Banten in January 2012. Infected plants in the field showed root and stem rot, discoloration of stems and/or branches. Severe infection may cause wilting of foliage then plant dried out. Based on microscopic observation Macrophomina phaseolina was constantly associated with diseased plants from those two areas. Hot temperature and low rainfall might favour disease development. This is the first report of charcoal rot disease of peanut in West Java and Banten. Key words: charcoal rot, Macrophomina phaseolina, peanut